Healing Process Following Application of Set or Fresh Mineral Trioxide Aggregate as a Root-End Filling Material - Habibi, Mehdi; Ghoddusi, Jamileh; Habibi, Ataollah; Mohtasham, Nooshin (European Journal of Dentistry, 2011)
Objectives: An unsuccessful attempt to reach the apical area or to place the retrograde material is a major difficulty in periradicular surgery. The aim of this study was to compare the histological evaluation of the healing process following an orthograde versus a retrograde application of mineral trioxide aggregate (MTA) as a root-end filling material during apical surgery on cats’ teeth in order to find out whether orthograde placement of MTA before surgery can be used instead of retrograde placement during surgery. Methods: In this experimental study, 24 canine teeth in 12 mature and healthy cats were filled with either MTA or gutta-percha in an orthograde manner. Two weeks later, the teeth with MTA were surgically exposed and resected to the set-MTA within the canals. The teeth previously filled by gutta-percha were also surgically exposed, and retrograde cavities were prepared at the root ends and filled with fresh-MTA. After 8 weeks, the animals were euthanized by vital perfusion. Six-micron histological slices were prepared from samples, stained by Hematoxylin & Eosin, and histologically studied by means of a light microscope. The collected data was analyzed by the Chi-square and the T-test. Results: One of the samples in the fresh-MTA group was omitted during processing because of inappropriate sectioning. In the set-MTA group, 5 out of 12 showed chronic abscess, while in the fresh-MTA group, 2 out of 11 were discovered to have chronic abscess; however, no significant difference was observed (P>.05). Hard tissue healing (cementum, bone, cementum + bone formation) in the set-MTA and fresh-MTA groups were 7 out of 12 and 9 out of 11, respectively. While healing seemed more likely to occur in the fresh-MTA group, the difference was statistically insignificant (P>.05). The magnitude of bone, cementum, or bone and cementum formation showed slight differences between the two groups; however, the figures failed to show any marked differences (P>.05). Conclusions: Orthograde placement of MTA could be used as an obturation material before surgery. In this way, after root-end resection, there would be no need for root-end preparation and filling procedures. (Eur J Dent 2011;5:19-23)
Keywords: Healing; Mineral Trioxide Aggregate; Root end filling